2016
DOI: 10.1080/10826076.2016.1266500
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-related impurities in e-cigarette cartridges and refill e-liquids

Abstract: The nicotine used in e-cigarettes and refill e-liquids is extracted from tobacco, and its purity can vary depending upon manufacturer and grade. The US and European Pharmacopoeias make recommendations for the purity of nicotine intended for pharmaceuticals; however, there is no official purity recommendation for nicotine used in e-cigarettes. To date, there are few published reports on nicotine-related impurities in e-cigarettes and refill e-liquids. The objective of this work was to develop a sensitive, selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 10 publications
1
30
0
Order By: Relevance
“…e conditions of storage and conservation are also incriminated and can also be responsible for many unknown impurities. A recent study has shown that nicotine impurities increase under long-term storage conditions especially n-nicotine, cotinine, myosmine, and nornicotine [29].…”
Section: Resultsmentioning
confidence: 99%
“…e conditions of storage and conservation are also incriminated and can also be responsible for many unknown impurities. A recent study has shown that nicotine impurities increase under long-term storage conditions especially n-nicotine, cotinine, myosmine, and nornicotine [29].…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4, after two months, anatabine, anabasine and β-nicotyrine were immeasurable while the yields of cotinine, nornicotine and myosmine, which are usually indicators of the thermal decomposition of nicotine (30)(31)(32), did not show noticeable changes. However, the yields of nicotine-N-oxide, which is the primary oxidation product of nicotine (25), increased quickly, especially under 40 °C / RH 75% storage condition. This experiment suggests that quantifying the yields of nicotine degradation products is an effective way to discern an unstable formulation.…”
Section: Stability Of Nicotine In Highly Flavored E-cigarette Productsmentioning
confidence: 99%
“…Pharmaceutical products are required to be comprehensively evaluated in rigorous stability studies to provide proof on how the quality, safety, and effectiveness of the drug products change with time under the influence of a variety of environmental factors such as temperature, humidity, and light (25,26). The stability studies, including real-time and accelerated tests, have been used to investigate the potential degradation products and impurities that originate from exposure and interaction with excipients, a specific container / closure system, and to ensure that the products retain their fitness for use up to the end of their expiration dates.…”
Section: Stability Of Nicotine In E-cigarette Products Under Various mentioning
confidence: 99%
“…Considering the addictive nature of nicotine, e-liquids need to be regulated for the total nicotine content as well as free base nicotine yield. ere are published methods for determining total nicotine content in e-liquids using gas chromatography and liquid chromatography coupled with mass detectors [27][28][29]. Recently, we have proposed a HPLC method based on peak purity criteria for accurate quantification of total nicotine content [19].…”
Section: Discussionmentioning
confidence: 99%